Perfection of technical maintenance management of aeronautical engineering - Тамаргазін, О. А. (Proceedings of National Aviation University, 2000)
Considered are the management perfection of system maintenance of aeronautical engineering by introduction of information systems, which are based on intellectual support of the users (management and technical staff of airline)